Model Integrasi Sains dan Agama dalam Kurikulum Muhammadiyah: Analisis Filosofis dan Pedagogis - Nurjaman, Fauzi; Jamroji, Bagus; Himmawan , Fajaruddin; Al Ishaq , Imam Abdimullah Al Ishaq; Rasyid , Muhammad Azhari (Educational Research Center, 2026)
This study aims to analyze the model of science and religion integration in the Muhammadiyah curriculum through a philosophical and pedagogical perspective. This study uses a qualitative approach with library research methods, which examines various primary and secondary sources in the form of scientific works, curriculum documents, and relevant previous research. The results of the study indicate that the integration of science and religion in the Muhammadiyah curriculum is based on the monotheistic paradigm that emphasizes the unity of sources of knowledge and rejects the dichotomy between religious knowledge and general knowledge. Philosophically, this integration serves as an epistemological and axiological foundation that directs the development of science so that it is oriented towards ethical values, spirituality, and the welfare of the community. Pedagogically, the integration of science and religion requires a contextual, reflective, and meaningful learning approach, emphasizing a balance between the domains of attitude, knowledge, and skills. Teachers have a strategic role as agents of integration and role models of values, not only as instructors but also as murabbi (leaders) who guide the character development of students. However, the implementation of science and religion integration still faces challenges, particularly the influence of digital culture, which tends to shift the orientation of education from character building to solely academic achievement. Therefore, strengthening the integrative paradigm and adaptive pedagogical innovation is an urgent need so that the Muhammadiyah curriculum can produce a generation that is intellectually superior, spiritually strong, and has noble morals.